Exploring medical and nursing students’ experiences of interprofessional communication and teamwork after a simulation-based interprofessional education session - Hoang Minh Nguyen; Vu Quoc Huy Nguyen; Minh Tam Nguyen; Khanh Vinh; Kyung Hye Park; Yon Chul Park (Korean Journal of Medical Education, 2026)
Interprofessional education (IPE) is increasingly implemented to prepare health professions students for collaborative practice. This exploratory pilot examined how medical and nursing students experienced and applied interprofessional communication and teamwork in clinical practice after a simulation based IPE session. This exploratory mixed-methods pilot study involved eight third year medical and nursing students at a Vietnamese medical university. Students completed the Students’ Perceptions of Interprofessional Clinical Education–Revised (SPICE R2) questionnaire before and after the session and submitted reflective essays 3 months later. Quantitative data were analyzed descriptively using Wilcoxon signed rank tests, and essays were examined using inductive reflexive thematic analysis. SPICE-R2 scores increased across all domains from preto post-test. The total median score rose from 3.90 (interquartile range [IQR], 3.83–4.38) to 4.60 (IQR, 4.40–4.83) (p=0.01). Thematic analysis generated five themes describing movement from parallel to shared care, greater use of structured communication, clearer appreciation of roles, recognition of shared responsibility for patient safety, and persisting barriers related to hierarchy and workload. This study suggests that a simulation-based IPE session can support students’ interprofessional communication and teamwork, though barriers related to hierarchy and workload persisted. Future research with larger, multi-institution samples and richer data sources is needed to understand how these skills are sustained in practice.